Clinical Profile and Role of Septic Screen in Early Onset Sepsis in a Tertiary Care Hospital of Western Nepal - A Prospective Observational Study - Gupta, Binod Kumar; Kaphle, Raju; Kurian, Buby Philip; Gupta, Badri Kumar (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: Neonatal sepsis is an important cause of neonatal mortality and morbidity with wide range of clinical manifestations. This study was aimed to study the clinical characteristics of sepsis along with the role of septic screen for early diagnosis of septicemia.MATERIAL AND METHODS: A prospective observational hospital based cross-sectional study was conducted in 113 screen positive newborns over a 12-month period at Universal College of Medical Sciences, Teaching Hospital Bhairahawa, Nepal.RESULTS: Out of 489 cases admitted to the NICU during the study period, 113 babies with screen positive sepsis were included in the study. Poor feeding (46%, n=52), respiratory distress (38.9%, n=44) and lethargy (30.1%, n=34) were top three clinical presentations in neonates with sepsis followed by seizures, jaundice, vomiting, fever and hypothermia respectively. 57.5% (n=65) of clinical sepsis cases enrolled had culture positivity with staphylococcus aureus in 41.5% (n=27) and Coagulase negative Staphylococcus (CONS) in 27.7% (n=18).  Klebsiella was the third common organism isolated in blood culture (23.1%, n=15).The sensitivities and specificities of two-test and three-test combinations in proven sepsis was calculated. Two-test combinations showed sensitivities between 33-100% and specificities between 30-90% whereas three-test combinations showed the sensitivities and specificities between 60-100% and 20-90% respectively.CONCLUSION: Poor feeding, respiratory distress and lethargy were common presentations in early onset neonatal sepsis. Three-test combination of septic screen had no overall advantage over two-test combination in the present study.